Sampling in quantitative research - Khatiban, M; Abed Saeed, J; Ashtari, I (Advances in Nursing & Midwifery, 2007)
Abstract Introduction: Sampling is an important phase in research, which directly influences on applicability and generalizability of findings. Therefore, it is critical in research process. Purpose: The purpose of this review was to assess sampling methods in published articles at the first 3 issues of the Journal of "Nursing Research" in 2004. Materials and Methods: A checklist was first made by reviewing literature and all articles in the issues were chosen. A critical appraisal of literature review, methods, results and discussion of the articles was performed by the checklist. SPSS package was used for data analysis. Results: Findings showed that samples in most studies were healthy people. Published articles explained about the target population, accessible population, the number of subjects and their features. However, a systematic bias was observed in all studied studies. Conclusion: Most authors did not describe the sampling method of their studies completely. This may make the critical review of sampling design, duplication of study and future meta-analysis hard. In addition, sample representativeness, sampling errors and systematic bias cannot be thoroughly evaluated. In most articles, authors referred to limitations resulted from failure in sampling design, which may restrict generalization. Keywords: Research Critique, Sampling.